2021
DOI: 10.1016/j.isci.2021.102354
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of biological noise in the flagellar length control system

Abstract: Any proposed mechanism for organelle size control should be able to account not only for average size but also for the variation in size. We analyzed cell-to-cell variation and within-cell variation of length for the two flagella in Chlamydomonas, finding that cell-to-cell variation is dominated by cell size, whereas withincell variation results from dynamic fluctuations. Fluctuation analysis suggests tubulin assembly is not directly coupled with intraflagellar transport (IFT) and that the observed length fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 86 publications
3
39
0
Order By: Relevance
“…CC-1690 and CC-5325 also had some differences in cilia length and swimming speed ( Figure 10 ). CC-5325 had longer cilia in TAP medium than CC-1690, consistent with the increased cell volume of CC-5325 in TAP as compared to CC-1690 ( Figure 1 ), as ciliary length scales with cell size [ 79 ]. CC-5325 had slower swimming speed in M-N medium than CC-1690, which may be related to additional influences by positive gravitaxis (downward swimming in response to gravity), as we observed that CC-5325 gravitaxed and settled faster than CC-1690 in both TAP and M-N medium.…”
Section: Discussionmentioning
confidence: 55%
“…CC-1690 and CC-5325 also had some differences in cilia length and swimming speed ( Figure 10 ). CC-5325 had longer cilia in TAP medium than CC-1690, consistent with the increased cell volume of CC-5325 in TAP as compared to CC-1690 ( Figure 1 ), as ciliary length scales with cell size [ 79 ]. CC-5325 had slower swimming speed in M-N medium than CC-1690, which may be related to additional influences by positive gravitaxis (downward swimming in response to gravity), as we observed that CC-5325 gravitaxed and settled faster than CC-1690 in both TAP and M-N medium.…”
Section: Discussionmentioning
confidence: 55%
“…Further, related strategies may be used to control the growth of radial microtubule arrays that reach the cell periphery (27,28), and may explain the scaling relationships observed between flagellar length and cell length (29) and between contractile ring diameter and cell diameter (30).…”
mentioning
confidence: 99%
“…As described in the introduction, a scale invariant protein gradient is useful to a cell that is in need of determining position within the cell relative to its linear dimensions, such as in the case of patterning in development [1]. Another possible use for such a gradient could be in controlling the self-assembly of linear structures such as actin cables and flagella, which are precisely scaled to the linear dimensions of the cell [29], [30], [31]. For example, a recent study of actin cables in yeast found that when cells were mutated to grow abnormally large, the actin cables assembled to a length that was proportional to the cell radius [32].…”
Section: Discussionmentioning
confidence: 99%